Curcumin and Derivatives in Nanoformulations with Therapeutic Potential on Colorectal Cancer - Sourour Idoudi (14153457) (2022)
There is growing concern in the rise of colorectal cancer (CRC) cases globally, and with this rise is the presentation of drug resistance. Like other cancers, current treatment options are either invasive or manifest severe side effects. Thus, there is a move towards implementing safer treatment options. Curcumin (CUR), extracted from Curcuma longa, has received significant attention by scientists as possible alternative to chemotherapeutic agents. It is safe and effective against CRC and nontoxic in moderate concentrations. Crucially, it specifically modulates apoptotic effects on CRC. However, the use of CUR is limited by its low solubility and poor bioavailability in aqueous media. These limitations are surmountable through novel approaches, such as nanoencapsulation of CUR, which masks the physicochemical properties of CUR, thus potentiating its anti-CRC effects. Furthermore, chemical derivatization of CUR is another approach that can be used to address the above constraints. This review spans published work in the last two decades, with key findings employing either of the two approaches, in addition to a combined approach in managing CRC. The combined approach affords the possibility of better treatment outcomes but not widely investigated nor yet clinically implemented. Graphical Abstract Other Information Published in: AAPS PharmSciTech License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1208/s12249-022-02268-y